Downregulation of hepatic lncRNA Gm19619 improves gluconeogenesis and lipogenesis following vertical sleeve gastrectomy in mice - Zhipeng Fang; Mingjie Fan; Dongqiang Yuan; Lihua Jin; Yangmeng Wang; Lili Ding; Senlin Xu; Jui Tu; Eryun Zhang; Xiwei Wu; Zhen Bouman Chen; Wendong Huang (Communications Biology, 2023)
A hepatic lncRNA Gm19619, which is repressed by vertical sleeve gastrectomy but upregulated by obesity and fasting, regulates gluconeogenesis and lipid metabolism in mice through Foxo1-G6pc/Pck1 and Lepr signaling pathway respectively.